Pengaruh Lingkungan Kerja dan Work-Life Balance terhadap Kepuasan Kerja: Stres Kerja sebagai Variabel Intervening - Riza Anggun Suci Alni (Jurnal Syntax Admiration, 2024)
Employees are one of the crucial factors in a company. Companies must be able to pay attention to the physical and mental needs of their employees to achieve good performance. The work environment and work-life balance are factors that affect employee performance and job satisfaction. This study aims to examine the influence of the work environment and work-life balance on job satisfaction, work stress as an intervening variable. In this study, the sample used was PT Telen employees. The number of samples taken was 100 respondents of PT Telen employees specifically in the operational field. The data for this study were obtained using an online survey questionnaire via google form with a measurement scale using a 5-point Likert scale. This research is a descriptive study using quantitative methods. The analysis tool used is Structural Equation Modeling (SEM), with data analysis techniques using the Smart-PLS version 3.0 application. The results of the study indicate that the work environment and work-life balance have a good relationship with a significant negative effect on work stress, but the work environment and work-life balance have a positive and significant effect on job satisfaction. While work stress has a negative and significant relationship with job satisfaction, and work stress can mediate the influence of the work environment on job satisfaction.